Employment-related collective bargaining in Germany: Annual report 2001 - Dieter Sadowski; Oliver Ludewig; Florian Turk (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2001)
The latest trends and developments on employment-related collective bargaining in Germany during the reference period are analysed in this study. We start with a quantitative overview on recent collective agreements and then describe the main types of measures negotiated in the newly concluded collective agreements.
Keywords: J50; 330; collective agreements; quantitative overview